Taxonomic and nomenclatural notes on Ligularia ghatsukupa, L. leesicotal and L. rumicifolia (Asteraceae, Senecioneae) - Wang, Long; Luo, Hong-Yi; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
We clear up the taxonomic and nomenclatural confusion involving Ligularia ghatsukupa, L. leesicotal and L. rumicifolia (Asteraceae, Senecioneae). The independent specific status of Ligularia leesicotal, which has been previously placed in synonymy within L. rumicifolia, is reinstated. Ligularia rumicifolia (Good) S. W. Liu (1985) is the correct author citation, not L. rumicifolia S. W. Liu (1985). Ligularia ghatsukupa is found to be conspecific with L. rumicifolia and is thus synonymized.